Answer:
35
Explanation:
-5{3-2[1-4(3-2^2)]}
we work inside out
using PEMDAS
parenthesis, exponents, multiply and divide, add and subtract
the very most inside
(3-2^2)
do the exponents
3 - 4 = -1
replace where it was in the original equation
-5{3-2[1-4(-1)]}
take the next set of parenthesis (bracket are the same as parenthesis)
[1-4(-1)]
multiply
4*-1 = -4
1--4 = 1+4 = 5
replace where it was in the original equation
-5{3-2[5]}
next set of parenthesis
{3-2[5]}
3 - 10 = -7
replace where it was in the original equation
-5 {-7}
35